Climate change and public health: An evaluation framework for local government - E.S. Loud; G.R. Woolf; A. Ralph; T. Gadhia; A.M.D. Navaratnam; L. Watson; A. McGushin; E. Clissold; B. Hilton (Elsevier, 2024)
Objectives: To develop and pilot an evaluation framework for assessing the engagement of local government public health teams in England on climate change and sustainability. These teams are uniquely positioned to address local health impacts of climate change and promote health co-benefits of mitigation. No statutory framework currently exists to support their engagement in this agenda. Study design: Literature review and two cross sectional surveys. Methods: A group of public health professionals conducted a literature review and agreed on criteria based on statutory responsibilities and remit of these teams, available information, and opportunities for local government action. With the resulting framework, this group evaluated all 11 local governments in the East of England region, and then conducted a follow-up survey to assess the framework's impact and acceptability. Results: An evaluation framework was developed with 21 criteria in two sections. The first assessed overall local government action and leadership in climate change and sustainability, to understand the context in which the public health team was situated. The second assessed the climate change related actions undertaken by the public health team.All 11 local governments in the East of England region completed the evaluation. Results indicated inconsistencies in local public health team action on and engagement with climate change and health. Ten local governments completed the follow-up survey on acceptability and impact, reporting that the evaluation was easy to complete. Seven out of ten respondents found that the evaluation had influenced change or reflection within their organisation, for example through identifying gaps and prompting more collaboration between teams. Conclusions: This evaluation framework is a useful and acceptable tool to assess local government public health engagement and leadership on climate change and sustainability. If used more widely, it could help to support public health teams to advance much-needed action in this area.